2008
DOI: 10.4103/0970-0218.43230
|View full text |Cite
|
Sign up to set email alerts
|

A study of anemia among adolescent females in the urban area of Nagpur

Abstract: Objectives:To estimate the prevalence of anemia among adolescent females and to study the socio-demographic factors associated with anemia.Materials and Methods:A cross-sectional survey was conducted in an urban area under Urban Health Training Center, Department of Preventive and Social Medicine, Government Medical College and Hospital, Nagpur. A total of 296 adolescent females (10–19 years old) were included in this study. The study took place from October 2002 to March 2003 (6 months). Statistical analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
64
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(87 citation statements)
references
References 3 publications
13
64
7
Order By: Relevance
“…This study shows the influence of menstrual bleeding on anemia which is significant statistically as well as clinically. This finding diverges from the reports of study done in Nagpur-India [11] and Rajini [7] in 2010 which explicated that the menstrual bleeding was not an associating factor for anemia.…”
Section: Menarchecontrasting
confidence: 57%
See 1 more Smart Citation
“…This study shows the influence of menstrual bleeding on anemia which is significant statistically as well as clinically. This finding diverges from the reports of study done in Nagpur-India [11] and Rajini [7] in 2010 which explicated that the menstrual bleeding was not an associating factor for anemia.…”
Section: Menarchecontrasting
confidence: 57%
“…It coincides with the reports of Chowdry et al [11] and contradicts with the documentation of Rita Singh [9]. The mean weight is significantly less than that of others.…”
Section: Nutritional Statuscontrasting
confidence: 55%
“…10 Chaudhary et al have reported socio-economic status and literacy status of parents. 5 As the key factors associated with anemia. In study by Desalegn et al the key predictors of anemia among adolescent girls were non consumption of protein and high calories foods, lower socio economic status and presence of intestinal worms.…”
Section: Discussionmentioning
confidence: 99%
“…3 The prevalence of anemia is reported to be ranging between 30% to as high as 68.8% as reported by various community based studies across India. [4][5][6][7][8][9] This burden is comparatively similar and in some cases higher than prevalence reported from other developing countries.…”
Section: Introductionmentioning
confidence: 98%
“…28,31 However, some studies also indicated that there is no significant association of age of adolescent girls and anaemia. [32][33][34] On multiple regressions analysis shows that the age of adolescent, education of adolescent, religion, caste, income strata and region of residence is found to be associated with anaemia in adolescent girls which indicated in several earlier studies. 29,[35][36][37] A study highlighted that about 43% of the adolescent deaths are related to pregnancy.…”
Section: Discussionmentioning
confidence: 78%